2016
DOI: 10.2480/agrmet.d-15-00016
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term effects of soil moisture on soil respiration in an apple orchard

Abstract: Although CO 2 flux observations by eddy covariance technique have many advantages, the nocturnal CO 2 efflux remains uncertain. To complement these observations and clarify the carbon budget/dynamics of an apple orchard, we applied an open chamber method and measured the soil respiration rate in September 2006-July 2010 for 237 days. We analyzed the temperature and moisture dependency of the soil respiration rate. The daily soil respiration rate, when normalized by soil temperature, was maximum when soil moist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The National Aeronautics and Space Administration (NASA) Earth Ventures 1 Airborne Microwave Observatory of Subcanopy and Subsurface (AirMOSS; https://airmoss.jpl.nasa.gov/) is a new airborne P-band synthetic aperture radar (SAR) designed to provide direct retrievals of root-zone soil moisture (RZSM) up to 120 cm in depth (depth of penetration varies depending on the amount of vegetation cover) using active remote sensing (Tabatabaeenejad et al, 2015). As its name implies, RZSM is a critical soil moisture state variable that influences plant functioning, including photosynthesis (Xia et al, 2017), ecosystem respiration (Flanagan & Johnson, 2005), and soil respiration (Ito & Ishida, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The National Aeronautics and Space Administration (NASA) Earth Ventures 1 Airborne Microwave Observatory of Subcanopy and Subsurface (AirMOSS; https://airmoss.jpl.nasa.gov/) is a new airborne P-band synthetic aperture radar (SAR) designed to provide direct retrievals of root-zone soil moisture (RZSM) up to 120 cm in depth (depth of penetration varies depending on the amount of vegetation cover) using active remote sensing (Tabatabaeenejad et al, 2015). As its name implies, RZSM is a critical soil moisture state variable that influences plant functioning, including photosynthesis (Xia et al, 2017), ecosystem respiration (Flanagan & Johnson, 2005), and soil respiration (Ito & Ishida, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…When normalized by soil temperature, the daily soil respiration rate is highest when soil moisture is at the field capacity and linearly declines with an increase or reduction in soil suction (pF). As soil suction increases, the soil becomes dryer and vice versa (Ito and Ishida, 2016).…”
Section: Correlation Of Soil Properties and Soil Respiration Ratementioning
confidence: 99%
“…Moreover, mowed grass can be decomposed by microorganisms, resulting in enhanced soil respiration. Previously, we had observed soil respiration in the apple orchard for four years and found that it was strongly affected by the amount of mowed grass ( Ito and Ishida, 2016). However, few studies have discussed in the effect of grass mowing on the overall CO 2 flux of orchards.…”
Section: Introductionmentioning
confidence: 99%